OVERVIEW OF BUDGETARY SLACK GOVERNANCE -- BASED ON THE INFORMAL GOVERNANCE PERSPECTIVE - Jia Bin; Noorul Azwin Md Nasir; Zaminor Zamzamir@Zamzamin; Amira Jamil, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The existence of budgetary slack makes it difficult for budget management to play the expected function, and managers put their interests above the interests of the company through the implementation of budgetary slack behaviors, which allocates the company's budget resources unbalanced, increases the agency costs, and ultimately leads to a decline in the quality of the sustainable governance of the company. Scholars have conducted quite a lot of research on how to govern budgetary slack, aiming to find ways to effectively govern budgetary slack. Previous scholars have studied the governance of budgetary slack mainly from the perspective of formal governance, and the results are quite fruitful, but the problem of budgetary slack still exists and is getting worse. Few scholars have studied the governance of budgetary slack from the perspective of informal governance. This article argues that informal governance is a kind of implicit contract based on social relations and emotions, which is more capable of obtaining the unanimous recognition and common compliance of the whole company and may play an unexpected role in the governance of budgetary slack. Therefore, this article will use the literature review method to sort out the studies on informal governance and summarise the informal governance measures for governing budgetary slack, which is expected to provide valuable reference suggestions for company managers and business leaders.